基于混沌遗传算法的齿轮变速箱优化设计 - 王晓云; 原思聪; 罗丹 (Jixie chuandong)
A chaotic genetic algorithm based on genetic algorithm combined with chaotic theory is purposed to the complex and more parameters optimal problem of gear box.In the method,the initial population is produced by the ergodicity of chaotic and the optimization process is made small perturbations on individual populations by using the second carrier wave technology,optimal solution is obtained by jumping out of local minimum.The design examples show that,the method is not only efficient and precision for searching the global optimal solution,but also a efficient technique to solve complex optimizations problems.